2020
DOI: 10.20944/preprints202010.0310.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanisms of Ras Membrane Organization and Signaling: Ras Rocks Again

Abstract: Ras is the most frequently mutated oncogene and recent drug development efforts have spurred significant new research interest. Here we will review progress toward understanding how Ras functions in nanoscale, proteo-lipid signaling complexes on the plasma membrane, called nanocluster. We will discuss how G-domain reorientation is plausibly linked to Ras-nanoclustering and -dimerization. We will then look at how these mechanistic features could cooperate in the engagement and activation of RAF by Ras. Moreover… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 81 publications
(152 reference statements)
0
5
0
1
Order By: Relevance
“…There is substantial interest in assessing the ability of RAS molecules to dimerize ( 11 13 ) or colocalize ( 14 17 ) at the membrane, because RAS-dependent RAF activation requires dimerization of RAF ( 18 20 ). Although wild-type KRAS4b, a common splice variant of KRAS (hereafter referred to as RAS), does not dimerize on two-component supported lipid bilayers ( 21 ), it preferentially colocalizes with anionic lipids in the liquid-disordered domains of giant unilamellar vesicles ( 22 ) and clusters on the scale of tens of nanometers in extracted PM sheets ( 14 , 23 , 24 ).…”
mentioning
confidence: 99%
“…There is substantial interest in assessing the ability of RAS molecules to dimerize ( 11 13 ) or colocalize ( 14 17 ) at the membrane, because RAS-dependent RAF activation requires dimerization of RAF ( 18 20 ). Although wild-type KRAS4b, a common splice variant of KRAS (hereafter referred to as RAS), does not dimerize on two-component supported lipid bilayers ( 21 ), it preferentially colocalizes with anionic lipids in the liquid-disordered domains of giant unilamellar vesicles ( 22 ) and clusters on the scale of tens of nanometers in extracted PM sheets ( 14 , 23 , 24 ).…”
mentioning
confidence: 99%
“…20,24,[48][49][50][51][52][53] Dimerization is critical for the activity of WT K-Ras as well as for the oncogenic ability of mutant G12D K-Ras. 60 Ras dimers have been observed in the biological assembly of an X-ray crystal structure 64 and NMR-inspired structures, 61 and different dimer interfaces have been suggested using both computational and experimental methods for members of the Ras family, 52,53 but still the exact structure of the KRAS dimer has not been experimentally resolved in the presence of its effector proteins.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recently, another approach for targeting K-Ras4B arose from cumulative evidence that membrane-bound K-Ras proteins, including K-Ras4B, form dimers or even nanoclusters in order to activate signaling pathways, with the dimer proposed to be the basic clustering unit. 20,24,[48][49][50][51][52][53] K-Ras dimerization aids the regulation of signaling pathways by providing signaling specificity, allosteric effects, and effector activation and inhibition. Indeed, it has been shown that WT K-Ras acts as a tumor suppressor in KRAS mutant cancer cells 54 by antagonizing the function of oncogenic K-Ras when forming WT-mutant dimers, which however no longer occurs when the WT KRAS allele is lost during tumor progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Білок SOS здійснює переведення Ras в активну GTP-форму. Протилежний процес -гідроліз GTP і переведення Ras у неактивну форму -GDP-Ras, знаходиться під контролем білка-активатора GTP-азної активності GAP (GTPase-Activating Protein) [32,33]. Сенс такої складної системи регуляції зрозумілий -адже активація/інактивація Ras лежить в основі процесів, здатних ініціювати, залежно від обставин, процес поділу клітин або механізму загибелі клітини шляхом апоптозу.…”
unclassified